LEGAL PROTECTION FOR NURSES IN IMPLEMENTING PROFESSIONAL AND INDEPENDENT HEALTH SERVICES (STUDY AT MURNI TEGUH MEMORIAL HOSPITAL) - Yusuf Sitinjak; Mhd. Azhali Siregar; Bambang Fitrianto (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Health services are defined as the provision of health efforts in a series of maintenance and improvement of personal health levels, all health service activities are carried out based on legal principles contained in binding regulations.Nursing as an integral part of health services has great leverage in health development efforts.The purpose of this study is to determine and examine the role and responsibilities of nurses in the implementation of professional and independent health services, and to determine and examine legal protection for nurses in the implementation of professional and independent health services. The preparation of this Thesis uses the Normative-Empirical Research Method used in the form of literature, journals, scientific articles and laws and regulations as well as related documents from various written sources related to the research and supported by empirical research in the form of interview results with various related parties. Then analyzed using qualitative analysis techniques and presented descriptively. The results of this study are: (1) The function of nurses in nursing practice consists of independent functions, interdependent functions and dependent functions. In relation to these functions, nurses have the ability to be responsible in carrying out their functions; (2) Legally, the nursing profession receives legal protection based on Article 53 paragraph (1) of Law Number 23 of 1992 and Article 1367 paragraph (1) of the Civil Code and Article 1367 paragraph (3). Based on these findings, Article 273 of Law Number 17 of 2023 concerning Health provides legal protection for health workers and medical personnel who carry out medical actions in health services. Health workers who are proven to be negligent can be subject to legal sanctions as referred to in Article 440 paragraphs (1) and (2); However, before being subject to criminal sanctions, the problem must be resolved through non-judicial channels as referred to in Article 310 of the Law. Medical personnel are not subject to sanctions if they can provide evidence that their work and actions are in accordance with professional standards, professional service standards, operational procedure standards, professional ethics, and patient requirements.